Linnaeus' Philosophia botanica - Linné, Carl von; Freer, Stephen (Oxford University Press, 2002)
In this new translation of Philosophia Botanica, example pages from Linnaeus' original Latin text are presented alongside Stephen Freer's English translation of the complete text. The book contains images of all eleven of the original plates, which illustrate the shapes of leaves and other plant structures and forms. Also included are Linnaeus' exp.